Tumor-Derived Exosomal RNA From Fine-Needle Aspiration Supernatant as a Novel Liquid Biopsy for Molecular Diagnosis of Cancer - Guorong Li; Dongdong Liu; Pascale Flandrin; Yang Zhang; Claude Lambert; Nora Mallouk; Michèle Cottier (Frontiers Media S.A., 2022)
Background: We hypothesized that the fine needle aspiration (FNA) supernatant from tumor might contain tumor-derived exosomes. The objective of this pilot study was to test if tumor-derived exosomal RNA could be found in FNA supernatants for molecular diagnosis of cancer.Methods: 10 FNA samples from pancreatic tumor were included. After the routine recuperation of cellular material by centrifugation, the cell-free Cytolyt liquid was collected instead of being discarded. 10 ml Cytolyt was used to isolate the exosomes. Transmission electronic microscopy (TEM) was used to examine the presence of exosomes. The exosomal marker CD63 was analyzed by flow cytometry. The exosomal RNA was extracted. RT-qPCR was performed to detect the GAPDH and the tumor marker of glypican 1 gene expression.Results: TEM confirmed the presence of exosomes from FNA supernatants. Flow cytometry showed a strong positive expression of exosome marker CD63. The concentration of exosomal RNA ranged from 18.81 to 354.75 ng/μl with an average of 81.76 ng/μl. The average exosomal RNA quantity was 1390.01 ng (range from 319.77 to 6030.75 ng) with an average 260/280 ratio of 2.12. GAPDH was detectable in all samples. Exosomal glypican 1 was detected in all samples of pancreatic ductal adenorcarcinomas (3/3) and absent from benign cystic samples (3/3). Furthermore, exosomal glypican 1 was positive in one sample with a non-contributive cytology and in one sample in which no malignant cell was found.Conclusion: This is the first report that the supernatants from FNA biopsy may contain tumor-derived exosomal RNA. These tumor-derived exosomes from FNA may provide a new liquid biopsy for the molecular diagnosis of cancer.